2000
DOI: 10.1161/01.hyp.36.4.549
|View full text |Cite
|
Sign up to set email alerts
|

Development of Hypertension Induced by Subpressor Infusion of Angiotensin II

Abstract: Abstract-Long-term administration of a subpressor dose of angiotensin II (Ang II) leads to pressor hyperresponsiveness and slow development of hypertension. Our preliminary data show that mRNA expression for calcitonin-gene related peptide in dorsal root ganglia was significantly increased by subpressor infusion of Ang II. To determine the role of sensory nerves in the development of hypertension induced by subpressor infusion of Ang II, newborn Wistar rats were given 50 mg/kg SC capsaicin on the 1st and 2nd d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
0

Year Published

2005
2005
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 23 publications
1
14
0
Order By: Relevance
“…We [55] found that the AT1 receptor content in the adrenal gland was not altered in any of the experimental groups, strongly suggesting that insufficiently suppressed PAL is a reflection of insufficiently suppressed circulating and/or tissue AII levels. In contrast to above mentioned studies that define the role of the RAAS in the development of hypertension in capsaicin treated rats fed a high-salt diet, we studied the role of sensory nerves in attenuating the development of hypertension induced by AII infusion [56] . AII or vehicle-infused rats were pretreated with capsaicin or vehicle.…”
Section: Vr1-positive Sensory Nerves and Increased Salt Sensitivitymentioning
confidence: 99%
“…We [55] found that the AT1 receptor content in the adrenal gland was not altered in any of the experimental groups, strongly suggesting that insufficiently suppressed PAL is a reflection of insufficiently suppressed circulating and/or tissue AII levels. In contrast to above mentioned studies that define the role of the RAAS in the development of hypertension in capsaicin treated rats fed a high-salt diet, we studied the role of sensory nerves in attenuating the development of hypertension induced by AII infusion [56] . AII or vehicle-infused rats were pretreated with capsaicin or vehicle.…”
Section: Vr1-positive Sensory Nerves and Increased Salt Sensitivitymentioning
confidence: 99%
“…In the RAS, angiotensinogen (AGT) is metabolized into Ang I, and Ang I is then converted to Ang II by Ang converting enzyme (ACE) (Paul et al, 2006;Campbell, 2014). The evidence indicates that Ang II, a main bioactive component of the RAS, affects a wide range of central and peripheral components of the sensory systems (Wu et al, 2000;Burkhalter et al, 2001;Pelegrini-da-Silva et al, 2005), and is mediated by Ang II type 1 (AT1) and Ang II type 2 (AT2) receptors.…”
Section: Introductionmentioning
confidence: 99%
“…There is substantial evidence that Ang II through its receptors can regulate the central and peripheral components of sensory systems (Buck et al 1982;Pelegrini-da-Silva Martins and Prado 2005;Saavedra 1992;Wu et al 2000). Recently, the presence of intraneuronal angiotensinergic system and Angiotensin II receptor type 1 (AT 1 ) has been documented in rat dorsal root ganglia (DRGs) (Patil et al 2010;Pavel et al 2008;Tang et al 2008), the structures containing primary afferent neurons that convey sensory information from periphery to the CNS.…”
Section: Introductionmentioning
confidence: 99%